Racial and Ethnic Residential Segregation by Family Structure and the Presence of Children in Metropolitan America - Friedman, Samantha (Race and social problems, 2022)
Little research has examined the residential segregation of blacks, Hispanics, and Asians from whites disaggregated by family structure and the presence of children in metropolitan America. Using data from the 2010 Census and the 2006–2010 American Community Survey, we find that, net of controls, among blacks, single-mother families are significantly more segregated from whites than married couples, regardless of the presence of children. However, these same differences in segregation are not found among Hispanics and Asians. Among those groups, married families with children under 18 are more segregated from whites than married families without children under 18, suggesting that married Hispanics and Asians with children desire closer proximity to their co-ethnics. The results suggest that racial and ethnic segregation by family structure and the presence of children varies by the racial and ethnic group considered and is, therefore, important to understanding overall racial and ethnic segregation in metropolitan America.